ROSYJSKA NEONOWOMOWA. ANALIZA PRZEMÓWIENIA W. W. PUTINA Z OKAZJI OBCHODÓW DNIA ZWYCIĘSTWA - Dudek-Waligóra, Gabriela (Przegląd Wschodnioeuropejski, 2024)
This article aims to analyze the speech of V. V. Putin delivered during the Russian national holiday – Victory Day. The study was conducted on the basis of the properties of newspeak distinguished by Polish researchers. The term “newspeak” was clarified, under which we understand the language of power used for the purposes of political propaganda in a totalitarian or authoritarian system. Observations of researchers about the authoritarian nature of the political system of contemporary Russia, the ideological assumptions adopted by the authorities, as well as the basic goals of Russian propaganda were quoted. It has been shown that the speech of the current Russian president of May 9, 2022 contains characteristic features attributed to the communist variant of newspeak in the literature on the subject. The examined speech of V. V. Putin is a created construct subordinated to the ideological vision of reality and trying to achieve the well-known goals of Russian propaganda.